Investigation of the Resistance Against the Fusarium solani at Different Pea Varieties and Combinations of Breeding - Mendlerné Drienyovszki, Nóra; Mándi, Lajosné (Acta Agraria Debreceniensis, 2003)
The Fusarium species are soil and polyphage parasits, and the rate of damage, caused by them, highly depend on interactions between climatic and edaphic factors and also on sensitivity of cultivars. Even though about 70-80 percent of the widely grown green peas cultivars is resistant to Fusarium oxysporum f. sp. pisi 1. race, the rate of Fusarium infections and severity of symptoms increased in the latest years. It is supposed that another Fusarium sp. the Fusarium solani has been spreading. The most exact way to study the cultivars in a provoking garden established in natural environment, where the pathogen is artificially enriched to a level, at which the cultivars can be distinguished according to their susceptibility. In the provoking garden the reaction against to Fusarium of our breeding lines and our registered cultivars and cultivars existed on the National List (including cultivars with well-known susceptibility as standards) are examined year by year. In our experiments we could found two green peas cultivars to be resistant to Fusarium solani (Early sweet (13,36%) and Lora (16,9%)) The breeding lines Margit and 8607/75-3-2 proved to be the most susceptible to Fusarium solani (94,4% and 73,1% infected plants, respectively).